2023
DOI: 10.1186/s12886-023-02840-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atropine and tropicamide on ocular biological parameters in children: a prospective observational study

Abstract: Background The effectiveness of cycloplegia in delaying the progression of myopia and its application in refractive examination in children have been extensively studied, but there are still few studies on the effects of atropine/tropicamide on ocular biological parameters. Therefore, the purpose of this study was to explore the effects of atropine/tropicamide on children's ocular biological parameters in different age groups and the differences between them. Meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…Previous studies have shown that the changes in ocular biometric parameters before and after mydriasis are smaller than diopters ( 16–18 ). Tao et al ( 19 ) found that even in young children who use atropine for mydriasis, there is no significant change in ocular biometric parameters. The invention of the optical coherence tomography (OCT) biometer has enabled non-invasive and easy measurement of ocular biometric parameters, which can be better accepted by subjects and their families and serve as a good objective indicator for evaluating refractive status.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the changes in ocular biometric parameters before and after mydriasis are smaller than diopters ( 16–18 ). Tao et al ( 19 ) found that even in young children who use atropine for mydriasis, there is no significant change in ocular biometric parameters. The invention of the optical coherence tomography (OCT) biometer has enabled non-invasive and easy measurement of ocular biometric parameters, which can be better accepted by subjects and their families and serve as a good objective indicator for evaluating refractive status.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to AL measurements, previous studies have shown no significant effect of tropicamide or phenylephrine on both cataract patients and children. [42][43][44] However, Cheng et al 45 observed an increase in AL following the instillation of tropicaminde. While the use of atropine (1%) did not produce a significant change in AL, 46,47 the same concentration being instilled one to two times a day for 1 week resulted in choroid thickening at the fovea in healthy myopic children.…”
Section: Regionmentioning
confidence: 99%
“…It has also been found that spending much more time outdoors delays the onset of myopia [14]. There are also pharmaceutical options such as atropine, although several studies have reported that the discontinuation of the treatment cause a risk of reduced accommodation and increased rebound of axial elongation [15], [16], [17].…”
Section: Introductionmentioning
confidence: 99%